Proportion detection method for double-layer coated pole piece
By configuring the slurry and optimizing the coating process in the ratio detection method of the double-layer coated electrode sheet, the problem of difficult to confirm the graphite ratio in the double-layer coating process is solved, and the energy density and cycle stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202510016574.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the double-layer coating process, it is difficult for existing technologies to confirm the ratio of two different types of graphite online, resulting in difficult protection of the consistency and stability of the coating.
A proportional detection method for double-layer coated electrode sheets is adopted, including configuring slurry, applying different proportions of graphite on the electrode sheets through the coating die head, and verifying different compaction densities, and finally performing OI value measurement and cyclic performance comparison on the electrode sheets of different compaction densities.
By accurately configuring the slurry and optimizing the coating process, the energy density, cycle stability and comprehensive performance of the battery are significantly improved, ensuring the consistency between the coating parameters and the set value.
Smart Images

Figure CN119574598A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode double-layer coating applications, and in particular to a ratio detection method for double-layer coated electrode sheets. Background Art
[0002] In the application of double-layer coating technology for negative electrode materials, graphite with excellent fast charging performance is usually selected for the outer layer, while high-capacity and high-compactness graphite is selected for the bottom layer, so as to take into account the needs of fast charging performance and high energy density performance. In the double-layer coating technology, there is a variety of ratios of the two graphites. In order to ensure the consistency of performance after coating, this patent introduces a new technology that can accurately determine the ratio of the upper and lower layers in the double-layer coating and ensure the consistency of the coating parameters with the set values.
[0003] In contrast, in the single-layer coating process, the negative electrode material is single, so the consistency of the coating surface density can be ensured through online monitoring, and the corresponding ratio can be determined accordingly. However, in the double-layer coating process, since two different types of graphite are used, the existing technical means are difficult to confirm the ratio of the two types of graphite online, and thus cannot ensure the consistency and stability of the coating. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art. To achieve the above purpose, a ratio detection method for a double-layer coated electrode is adopted to solve the problems raised in the above background technology.
[0005] A method for detecting the ratio of a double-layer coated electrode comprises the following steps:
[0006] Step S1, preparing slurry: preparing CMC glue and stirring, and adding SWCNT conductive glue at the same time; then adding the main material and SP, and stirring at high speed, and finally adding SBR emulsion and stirring at low speed, and adjusting according to the viscosity requirement range to obtain the final slurry;
[0007] Step S2, coating different proportions of graphite on the pole piece through a coating die head according to the final slurry obtained, and verifying the pole piece with different compaction densities;
[0008] Step S3: The OI values of the pole pieces with different compaction densities are measured, and the cycle performances of the measurement results are compared to obtain comparison results of different cycle data.
[0009] As a further solution of the present invention: the specific steps in step S1 include:
[0010] Step S11, the obtained CMC glue solution is glued, and stirred according to the preset solid content m1, stirring speed v1, and time t1 to prepare the CMC glue solution, and a portion of the CMC glue solution is obtained;
[0011] Step S12, obtaining SWCNT slurry, and stirring it according to a preset stirring speed v2 and time t2 to prepare a conductive adhesive solution;
[0012] Step S13, adding the first part of the main material, stirring according to the preset stirring speed v3 and time t3, and then adding SP and the second part of the main material;
[0013] Step S14, adding part of the glue solution in step S11 to the obtained SWCNT slurry, and stirring at a high speed according to a preset stirring speed v4 and time t4;
[0014] Step S15, adding SBR emulsion, stirring at a low speed according to a preset stirring speed v5 and time t5;
[0015] Step S16: Finally, the viscosity is controlled according to the range f of the viscosity requirement of the process standard slurry to obtain the final slurry. By refining each sub-step in step S1 and setting specific parameters, such as stirring speed, time and solid content, the slurry preparation process can be more accurately controlled, thereby improving the quality and stability of the slurry.
[0016] As a further solution of the present invention: the specific steps in step S11 include:
[0017] Obtain the slurry ratio and perform glue treatment on the obtained CMC;
[0018] During the gluing process, according to the predetermined ratio, the CMC solid content m1 is determined to be 1.65%, the stirring speed v1 is 30 / 30 Hz, the stirring time t1 is 3h, stirring is performed to obtain CMC glue, and 40% of the CMC glue is taken out.
[0019] As a further solution of the present invention: the stirring speed v2 in step S12 is 30 / 30 Hz, and the time t2 is 2 h.
[0020] As a further solution of the present invention: the stirring speed v3 in step S13 is 10 / 5 Hz, and the time t3 is 30 min. These specific parameters and steps ensure the uniform mixing of CMC glue, SWCNT slurry and main materials, providing a guarantee for the preparation of high-quality slurry.
[0021] As a further solution of the present invention: the specific steps in step S14 include:
[0022] 40% of the CMC glue taken out in step S11 is added to the slurry, and high-speed stirring is performed at a stirring speed v4 of 35 / 30 Hz and a time t4 of 2 h. Low-speed stirring can prevent the particles in the slurry from being destroyed, while ensuring the uniform distribution of the SBR emulsion, further improving the performance of the slurry.
[0023] As a further solution of the present invention: the specific steps in step S15 include:
[0024] The slurry after high-speed stirring in step S14 is added with SBR emulsion, and high-speed stirring is performed at a stirring speed v5 of 12 / 10 Hz and a time t4 of 1 hour. High-speed stirring can further ensure uniform mixing of CMC glue and SWCNT slurry, thereby improving the stability and performance of the slurry.
[0025] As a further solution of the present invention: the specific steps in step S16 include:
[0026] The viscosity of the process standard slurry is controlled within the range f of 5000-7000 mPa·s, and when f exceeds the process standard, it is adjusted to obtain the final slurry. Viscosity control can ensure that the viscosity of the slurry is within the process standard range, thereby meeting the needs of subsequent coating and battery production.
[0027] As a further solution of the present invention: the specific steps in step S2 include:
[0028] Step S21: First, a single-layer coating technique is used, with the upper layer being graphite A and the bottom layer being graphite B, wherein the surface density is controlled at 90-120 g / m 2 within the scope of
[0029] Step S22: Secondly, a double-layer coating die is used for coating, wherein the upper layer of the double layer is graphite A and the lower layer is graphite B, and the double-layer coating is performed in different proportions, and the surface density ranges from 180 to 240 g / m 2 between;
[0030] Among them, the upper slurry ratio is graphite A: CMC: SP: SWCNT: SBR = 96.73%: 1.25%: 1.0%: 0.02%: 1.0%;
[0031] The ratio of the lower slurry is graphite B: CMC: SP: SWCNT: SBR = 96.18%: 1.25%: 0.7%: 0.02%: 1.85%;
[0032] Step S23: Verify the prepared pole piece at different compaction densities. Through single-layer coating and double-layer coating technology, the best coating method and graphite ratio can be explored, thereby improving the energy density and performance of the battery.
[0033] As a further solution of the present invention: the specific steps in step S3 include:
[0034] Step S31, measuring the OI value of the pole pieces with different compaction densities in step S2 by using an XRD device to obtain the measurement result of the OI value;
[0035] Step S32, obtain the measurement result of OI value, and obtain the comparison results of different cycle data according to the ratio of double-layer coating. Through OI value measurement and cycle performance comparison, we can deeply understand the influence of different compaction density and coating ratio on battery performance, and provide strong support for optimizing battery design.
[0036] Compared with the prior art, the present invention has the following technical effects:
[0037] By adopting the above-mentioned technical scheme, the slurry including CMC glue, SWCNT conductive glue, main material, SP and SBR emulsion is accurately configured and adjusted according to the viscosity requirements. Then, different proportions of graphite are coated on the pole piece by a coating die and different compaction densities are verified. Finally, the OI value of the pole pieces with different compaction densities is measured and the cycle performance is compared, thereby optimizing the slurry configuration and coating process, and significantly improving the energy density, cycle stability and comprehensive performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings:
[0039] Figure 1 A schematic diagram of the steps of the ratio detection method of the embodiment disclosed in this application;
[0040] Figure 2 Schematic diagram of single-layer coating and double-layer coating of the embodiment disclosed in this application;
[0041] Figure 3 This is a schematic diagram for comparing the cycle performance of the embodiments disclosed in this application. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Please refer to Figure 1 In an embodiment of the present invention, a ratio detection method for a double-layer coated electrode piece includes the following steps:
[0044] Step S1, preparing slurry: prepare CMC glue and stir, and add SWCNT conductive glue at the same time; then add the main material and SP and stir at high speed, and finally add SBR emulsion and stir at low speed, and adjust according to the required viscosity range to obtain the final slurry. The specific steps include:
[0045] Step S11, the obtained CMC glue solution is glued, and stirred according to the preset solid content m1, stirring speed v1, and time t1 to prepare the CMC glue solution, and obtain part of the CMC glue solution; the specific steps include:
[0046] Obtain the slurry ratio and perform glue treatment on the obtained CMC;
[0047] During the gluing process, according to the predetermined ratio, the CMC solid content m1 is determined to be 1.65%, the stirring speed v1 is 30 / 30 Hz, the stirring time t1 is 3h, stirring is performed to obtain CMC glue, and 40% of the CMC glue is taken out.
[0048] Step S12, obtaining SWCNT slurry, and stirring it according to a preset stirring speed v2 and time t2 to prepare a conductive adhesive solution;
[0049] The stirring speed v2 is 30 / 30 Hz and the time t2 is 2 h.
[0050] Step S13, adding the first part of the main material, stirring according to the preset stirring speed v3 and time t3, and then adding SP and the second part of the main material;
[0051] The stirring speed v3 is 10 / 5 Hz, and the time t3 is 30 min.
[0052] Step S14, adding part of the glue solution in step S11 to the obtained SWCNT slurry, and stirring at a high speed according to a preset stirring speed v4 and time t4. The specific steps include:
[0053] The 40% CMC glue solution taken out in step S11 is added to the slurry, and high-speed stirring is performed at a stirring speed v4 of 35 / 30 Hz and a time t4 of 2 h.
[0054] Step S15, adding SBR emulsion, stirring at a low speed according to the preset stirring speed v5 and time t5. The specific steps include:
[0055] The slurry after high-speed stirring in step S14 is added with SBR emulsion, and high-speed stirring is performed at a stirring speed v5 of 12 / 10 Hz and a time t4 of 1 h.
[0056] Step S16: Finally, the viscosity is controlled according to the range f of the viscosity requirement of the process standard slurry to obtain the final slurry. The specific steps include:
[0057] The viscosity of the process standard slurry is controlled within the range f of 5000-7000 mPa·s, and when f exceeds the process standard, it is adjusted to obtain the final slurry. Viscosity control can ensure that the viscosity of the slurry is within the process standard range, thereby meeting the needs of subsequent coating and battery production.
[0058] Step S2: According to the final slurry obtained, different proportions of graphite are coated on the pole piece through a coating die, and the pole piece is verified at different compaction densities. The specific steps include:
[0059] like Figure 2 As shown, the figure shows a schematic diagram of single-layer coating and double-layer coating;
[0060] Step S21: First, a single-layer coating technique is used, with the upper layer being graphite A and the bottom layer being graphite B, wherein the surface density is controlled at 90-120 g / m 2 within the scope of
[0061] The OI values of negative electrode sheets with different compaction densities are calculated by rolling single-layer (upper and lower layers) graphite pole pieces at different compaction densities (compaction density ranges from 1.4-1.8g / cc). The OI value of double-layer coated pole pieces is calculated under certain pressure conditions, and the different compaction densities of the upper and lower layers in the double layer are calculated by combining the single-layer OI values with the double-layer OI values of different compaction densities, thereby ensuring that the deviation of the compaction density of different layers is less than 0.5%.
[0062] Step S22: Secondly, a double-layer coating die is used for coating, wherein the upper layer of the double layer is graphite A and the lower layer is graphite B, and the double-layer coating is performed in different proportions, and the surface density ranges from 180 to 240 g / m 2 between;
[0063] Among them, the upper slurry ratio is graphite A: CMC: SP: SWCNT: SBR = 96.73%: 1.25%: 1.0%: 0.02%: 1.0%;
[0064] The ratio of the lower slurry is graphite B: CMC: SP: SWCNT: SBR = 96.18%: 1.25%: 0.7%: 0.02%: 1.85%;
[0065] Step S23, verifying the prepared pole pieces at different compaction densities.
[0066] In this embodiment, the composition of the formula and the proportion is shown in the following table:
[0067]
[0068]
[0069]
[0070] According to the above, materials can be selected, specifically:
[0071] Negative electrode 1 / negative electrode 2: graphite, hard carbon, silicon carbon, etc.;
[0072] Binder 1 / Binder 2: CMC, SBR, PAA, styrene acrylic, etc.;
[0073] Conductive agent 1 / conductive agent 2: carbon black, carbon nanotubes, acetylene black, Ketjen black, VGCF, etc.;
[0074] Copper foil selection: 3-6 micron copper foil, copper foil width: 200-1400mm;
[0075] Step S3: Determine the OI value of the pole pieces with different compaction densities, and compare the cycle performance of the measurement results to obtain comparison results of different cycle data. The specific steps include:
[0076] Step S31, measuring the OI value of the pole pieces with different compaction densities in step S2 by using an XRD device to obtain the measurement result of the OI value;
[0077] In this embodiment, the OI value testing method is specifically as follows:
[0078] ① First, set the parameters of the XRD equipment, where the scanning range is 10-90°, the step size is 0.01, and the scanning speed is 5° / min to obtain XRD raw data;
[0079] ②. Use analysis software to obtain XRD peak intensity data, OI value = I004 / I110 (I002 / I110).
[0080] In this embodiment, the DOE designs of double-layer coating with different ratios are shown in the following table:
[0081]
[0082] Step S32, obtaining the measurement result of the OI value, and obtaining the comparison results of different cycle data according to the ratio of the double-layer coating.
[0083] In this embodiment, the measurement results are shown in the following table:
[0084]
[0085] In this embodiment, beneficial effects are:
[0086] The difference between the design value and the actual value of the double-layer coating ratio can be determined by the size of the OI value.
[0087] In addition, for the bottom graphite negative electrode, natural graphite can be used, which can greatly reduce the cost of artificial graphite, thereby reducing the cost of the entire battery cell and improving bargaining power.
[0088] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
[0089] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A method for detecting the ratio of a double-layer coated electrode, characterized in that: The following steps are involved: Step S1, preparing slurry: preparing CMC glue and stirring, and adding SWCNT conductive glue at the same time; then adding the main material and SP, and stirring at high speed, and finally adding SBR emulsion and stirring at low speed, and adjusting according to the viscosity requirement range to obtain the final slurry; Step S2, coating different proportions of graphite on the pole piece through a coating die head according to the final slurry obtained, and verifying the pole piece with different compaction densities; Step S3: The OI values of the pole pieces with different compaction densities are measured, and the cycle performances of the measurement results are compared to obtain comparison results of different cycle data.
2. A method for detecting the ratio of a double-layer coated electrode according to claim 1, characterized in that: The specific steps in step S1 include: Step S11, the obtained CMC glue solution is glued, and stirred according to the preset solid content m1, stirring speed v1, and time t1 to prepare the CMC glue solution, and a portion of the CMC glue solution is obtained; Step S12, obtaining SWCNT slurry, and stirring it according to a preset stirring speed v2 and time t2 to prepare a conductive adhesive solution; Step S13, adding the first part of the main material, stirring according to the preset stirring speed v3 and time t3, and then adding SP and the second part of the main material; Step S14, adding part of the glue solution in step S11 to the obtained SWCNT slurry, and stirring at a high speed according to a preset stirring speed v4 and time t4; Step S15, adding SBR emulsion, stirring at a low speed according to a preset stirring speed v5 and time t5; Step S16: Finally, the viscosity is controlled according to the range f of the viscosity requirement of the process standard slurry to obtain the final slurry.
3. A method for detecting the ratio of a double-layer coated electrode according to claim 2, characterized in that: The specific steps in step S11 include: Obtain the slurry ratio and perform glue treatment on the obtained CMC; During the gluing process, according to the predetermined ratio, the CMC solid content m1 is determined to be 1.65%, the stirring speed v1 is 30 / 30 Hz, the stirring time t1 is 3h, stirring is performed to obtain CMC glue, and 40% of the CMC glue is taken out.
4. A method for detecting the ratio of a double-layer coated electrode according to claim 3, characterized in that: The stirring speed v2 in step S12 is 30 / 30 Hz, and the time t2 is 2 h.
5. A method for detecting the ratio of a double-layer coated electrode according to claim 4, characterized in that: The stirring speed v3 in step S13 is 10 / 5 Hz, and the time t3 is 30 min.
6. A method for detecting the ratio of a double-layer coated electrode according to claim 5, characterized in that: The specific steps in step S14 include: The 40% CMC glue solution taken out in step S11 is added to the slurry, and high-speed stirring is performed at a stirring speed v4 of 35 / 30 Hz and a time t4 of 2 h.
7. A method for detecting the ratio of a double-layer coated electrode according to claim 6, characterized in that: The specific steps in step S15 include: The slurry after high-speed stirring in step S14 is added with SBR emulsion, and high-speed stirring is performed at a stirring speed v5 of 12 / 10 Hz and a time t4 of 1 h.
8. A method for detecting the ratio of a double-layer coated electrode according to claim 7, characterized in that: The specific steps in step S16 include: The viscosity is controlled within the range f of 5000-7000 mPa·s required by the process standard slurry, and when f exceeds the process standard, adjustment is made to obtain the final slurry.
9. A method for detecting the ratio of a double-layer coated electrode according to claim 1, characterized in that: The specific steps in step S2 include: Step S21: First, a single-layer coating technique is used, with the upper layer being graphite A and the bottom layer being graphite B, wherein the surface density is controlled at 90-120 g / m 2 within the scope of Step S22: Secondly, a double-layer coating die is used for coating, wherein the upper layer of the double layer is graphite A and the lower layer is graphite B, and the double-layer coating is performed in different proportions, and the surface density ranges from 180 to 240 g / m 2 between; Among them, the upper slurry ratio is graphite A: CMC: SP: SWCNT: SBR = 96.73%: 1.25%: 1.0%: 0.02%: 1.0%; The ratio of the lower slurry is graphite B: CMC: SP: SWCNT: SBR = 96.18%: 1.25%: 0.7%: 0.02%: 1.85%; Step S23, verifying the pole pieces prepared above at different compaction densities.
10. A method for detecting the ratio of a double-layer coated electrode according to claim 1, characterized in that: The specific steps in step S3 include: Step S31, measuring the OI value of the pole pieces with different compaction densities in step S2 by using an XRD device to obtain the measurement result of the OI value; Step S32, obtaining the measurement result of the OI value, and obtaining the comparison results of different cycle data according to the ratio of the double-layer coating.
Citation Information
Patent Citations
Quantitative test method for floating of SBR (sequencing batch reactor)
CN115436215A
Method for detecting mutual dissolution of upper-layer slurry and lower-layer slurry in double-layer coating
CN115931936A
Positive plate, lithium ion battery and preparation method
CN116864615A
Lithium battery negative plate as well as preparation method and application thereof
CN118248833A
Negative electrode double-layer coating process, negative electrode plate and lithium ion battery
CN118315523A